Hyperhomocysteinemia – A treatable cause of cerebral venous thrombosis in young - Vivekanand Kamat; Suresh Harsoor (APIK Journal of Internal Medicine, 2020)
Mild hyperhomocysteinemia is an established risk factor for deep vein thrombosis. Here, we report a case of a 28-year-old male with complaints of severe headache and vomiting for 7 days, and he also had two episodes of generalised tonic clonic seizures (GTCS) type of convulsions. Magnetic resonance imaging + magnetic resonance venography showed acute infarct with hemorrhagic transformation in the right occipital region and venous thrombosis of the right transverse sinus, right sigmoid sinus, and superior sagittal sinus. All laboratory investigations including protein C, S, and B12levels were found to be normal except for serum homocysteine which was 29.20 μmol/L. After anticoagulation therapy, this young patient completely recovered without any residual neurological deficit. Hence, we suggest that hyperhomocysteinemia should also be a risk factor for cerebral venous thrombosis (CVT). Since this condition can be effectively and safely corrected by drugs, we suggest that homocysteine levels should be routinely determined in patients with idiopathic CVT, and even mildly increased levels corrected pharmacologically, in the hope of reducing the risks associated with this condition.